Anti-PD-1 Therapy plus Chemotherapy and/or Bevacizumab as Second Line or later Treatment for Patients with Advanced Non-Small Cell Lung Cancer - Zhang, Fan (J Cancer, 2020)
Immune checkpoint inhibitor combination therapy exhibited outstanding efficacy in first line setting for advanced non-small cell lung cancer (aNSCLC) patients. However, whether PD-1 inhibitor combined treatment is effective in second line or later setting remains unknown. Therefore, we retrospectively evaluated the efficacy of combined therapy of PD-1 inhibitor with chemotherapy and/or bevacizumab compared to PD-1 inhibitor alone for aNSCLC patients in second line or later setting. Patients with aNSCLC who have received anti-PD-1 based therapy between 2015 and 2017 were screened, and 55 patients were ultimately included and divided into the monotherapy group (N=33) and the combination group (N=22). Patients treated with combination therapy exhibited superior PFS versus those treated with monotherapy (median PFS, 7.5 months vs 3.3 months; hazard ratio 0.28; 95% CI, 0.14-0.56; P<0.001). Objective response rate and disease control rate were 31.8% (7/22) and 95.5% (21/22) in the combination group and 10.0% (3/30) and 46.7% (14/30) in the monotherapy group, respectively (ORR, P=0.075; DCR, P<0.001). Five patients (22.7%) experienced grade 3-4 adverse events in the combination group and two patients (6.1%) in the monotherapy group. Taken together, our results indicated that for NSCLC patients who had failed on the first-line or later treatment, PD-1 inhibitor in combination with chemotherapy and/or bevacizumab might be a favorable treatment option. These findings warrant further validation in prospective studies.